Identification of hydrophobic amino acids required for lipid activation of C. elegans CTP:phosphocholine cytidylyltransferase - Braker, Jay D (2009)
CTP:phosphocholine cytidylyltransferase (CCT), critical for phosphatidylcholine biosynthesis, is activated by translocation to the membrane surface. The lipid activation region of Caenorhabditis elegans CCT is between residues 246 and 266 of the 347 amino acid polypeptide, a region proposed to form an amphipathic alpha helix. When leucine 246, tryptophan 249, isoleucine 256, isoleucine 257, or phenylalanine 260, on the hydrophobic face of the helix, were changed individually to serine low activity was observed in the absence of lipid vesicles, similar to wild-type CCT, while lipid stimulated activity was reduced compared to wild-type CCT. Mutational analysis of phenylalanine 260 implicated this residue as a contributor to auto-inhibition of CCT while mutation of L246, W249, I256, and I257 simultaneously to serine resulted in significantly higher activity in the absence of lipid vesicles and an enzyme that was not lipid activated. These results support a concerted mechanism of lipid activation that requires multiple residues on the hydrophobic face of the putative amphipathic alpha helix.